The Effect Of Work Discipline On Employee Performance At The Dairi Regency Regional Disaster Management Agency Office - Roy Endharto Tumanggor; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of Work Discipline on Employee Performance at the Dairi Regency Regional Disaster Management Agency Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 43 people taken by purposive sampling. The results of the study show that Work Discipline has a positive and significant effect on Employee Performance. This is shown by the T-count value of 43.223 > t table 2.01954, with a significance value of 0.000 < 0.05. The regression coefficient shows that if Work Discipline is increased by 1 unit, then Employee Performance will increase by 0.987 units assuming other variables are fixed. In addition, the results of the determination test showed an Adjusted R Square value of 0.960 or 96.00%, which indicates that Work Discipline has a very high influence on Employee Performance, while the remaining 4.00% is influenced by other factors that have not been studied. Thus, partially, Work Discipline has a positive and significant effect on Employee Performance at the Dairi Regency Regional Disaster Management Agency Office. This identifies that improvements in Work Discipline can contribute to improving Employee Performance